Implikasi Hukum Islam Terhadap Transaksi Ekonomi Digital - Nafisya, Zahwah Aulia; Sapa, Nasrullah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of the digital economy has transformed the landscape of global economic transactions, including in Muslim-majority countries. Phenomena such as e-commerce and digital assets (cryptocurrency, tokens, and NFTs) offer convenience and new opportunities in economic activities but also raise legal issues from the perspective of Sharia law. This study aims to analyze the position of the digital economy within Islamic economic law, examine the validity of e-commerce transactions based on the principles of fiqh al-mu‘āmalah, and assess the legal status of digital assets according to the views of scholars and fatwa institutions. The research method employed in this study is library research, which involves the analysis of books, scholarly works, and previous studies related to the topic. The findings indicate that e-commerce transactions are generally permissible as long as they fulfill the pillars and conditions of a valid sale contract and are free from elements of riba (usury), gharar (uncertainty), and deception. In general, the digital economy can be accepted within the framework of Islamic economic law if it is managed according to the principles of maqāṣid al-sharī‘ah, namely upholding justice, promoting public welfare, and protecting the wealth of the community. This study emphasizes the importance of strengthening Sharia-based regulations in governing the digital economy to ensure alignment with Islamic values and to contribute to the sustainable development of the Muslim community’s economy.